2001
DOI: 10.1016/s0921-4534(01)00886-3
|View full text |Cite
|
Sign up to set email alerts
|

Fast formation and superconductivity of MgB2 thick films grown on stainless steel substrate

Abstract: The fabrication, characterisation, and superconductivity of MgB 2 thick films grown on stainless steel substrate were studied. XRD, SEM, and magnetic measurements were carried out. It was found that the MgB 2 thick films can be fast formed by heating samples to 660 o C then immediately cooling down to room temperature. XRD shows above 90% MgB 2 phase and less than 10 % MgO. However, the samples sintered at 800 o C for 4 h contain both MgB 4 and MgO impurities in addition to MgB 2 . The fast formed MgB 2 films … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 10 publications
2
23
1
Order By: Relevance
“…It has been reported that the MgB can be formed by in-situ reaction between magnesium and amorphous boron in a very short time, as little as a few minutes at temperatures just above the melting point of magnesium [16], [17]. Furthermore, the samples sintered at temperatures above 750 C for only a few minutes are as good as those sintered for a long time.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the MgB can be formed by in-situ reaction between magnesium and amorphous boron in a very short time, as little as a few minutes at temperatures just above the melting point of magnesium [16], [17]. Furthermore, the samples sintered at temperatures above 750 C for only a few minutes are as good as those sintered for a long time.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there are many impurities (mainly Mg) on the surface of the film, which are formed during the synthesis of MgB 2 . Consequently, the giant flux jump of MgB 2 films is reduced further by these impurities [9,15]. Treiber et al, however, insisted that there are still flux jumps in the film around 12 K, even though their behavior was different from the jumps observed below 10 K [16].…”
Section: Resultsmentioning
confidence: 99%
“…Attempts to fabricate MgB 2 tapes with wide variety of metal substrates [7][8][9] along with the insertion of different dopants [10,11] and buffer layers [11,12] into MgB 2 tapes have been vigorously made in the past several years. Out of different processing conditions, MgB 2 grown on Hastelloy tape seems to have a good prospect in the industry due to the Hastelloy's flexibility and its low corrosiveness [8,[13][14].…”
Section: Introductionmentioning
confidence: 99%